Nanosecond Laser Etching of Surface Drag-Reducing Microgrooves: Advances, Challenges, and Future Directions - Xulin Wang; Zhenyuan Jia; Jianwei Ma; Wei Liu (Aerospace)
With the increasing demand for drag reduction, energy consumption reduction, and low weight in civil aircraft, high-precision microgroove preparation technology is being developed internationally to reduce wall friction resistance and save energy. Compared to mechanical processing, chemical etching, roll forming, and ultrafast laser processing, nanosecond lasers offer processing precision, high efficiency, and controllable thermal effects, enabling low-cost and high-quality preparation of microgrooves. However, the impact of nanosecond laser etching on the fatigue performance of substrate materials remains unclear, leading to controversy over whether high-precision shape control and fatigue performance enhancement in microgrooves can be achieved simultaneously. This has become a bottleneck issue that urgently needs to be addressed. This paper focuses on the current research status of nanosecond laser processing quality control for microgrooves and the research status of laser effects on enhancing the fatigue performance of substrate materials. It identifies the main existing issues: (1) how to induce surface residual compressive stress through the thermo-mechanical coupling effect of nanosecond lasers to suppress micro-defects while ensuring high-precision shape control of fixed microgrooves; and (2) how to quantify the regulation of nanosecond laser process parameters on residual stress distribution and fatigue performance in the microgroove area. To address these issues, this paper proposes a collaborative strategy for high-quality shape control and surface strengthening in fixed microgrooves, an analysis of multi-dimensional fatigue regulation mechanisms, and a new method for multi-objective process optimization. The aim is to control the geometric accuracy error of the prepared surface microgrooves within 5% and to enhance the fatigue life of the substrate by more than 20%, breaking through the technical bottleneck of separating “drag reduction design” from “fatigue resistance manufacturing”, and providing theoretical support for the integrated manufacturing of “drag reduction-fatigue resistance” in aircraft skins.